CLASSIFICATION OF DIGITAL TECHNOLOGIES USED IN LIGHT INDUSTRY ENTERPRISES AND THEIR IMPACT ON IMPROVING EFFICIENCY - Quldasheva Nargiza Komoliddin qizi (Modern American Journals, 2025)
This paper explores the classification and effectiveness of digital technologies in the light industry sector. It highlights the integration of technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), Augmented and Virtual Reality (AR/VR), blockchain, and digital twins in enhancing production automation, real-time monitoring, and personalized services. The study emphasizes the strategic role of digital transformation in improving operational efficiency and advancing the circular economy model.